Risk of intracranial hemorrhage in patients using anticoagulant therapy for atrial fibrillation after cerebral microbleeds combined with acute ischemic stroke: a meta-analysis - Zhao, Bingqing; Yuan, Ye; Li, Zheng; Chen, Ying; Gao, Yali; Yang, Baoling; Wu, Jingyi; Jia, Weihua (Frontiers in Neurology, 2024)
Objective: To evaluate intracerebral hemorrhage (ICH) risk in patients with ischemic stroke (IS) and cerebral microbleeds (CMBs) undergoing anticoagulation therapy for non-valvular atrial fibrillation (AF). Methods: We conducted a comprehensive search across multiple databases, including Embase, PubMed, Cochrane, Up To Date, Scopus, WOS, and SinoMed. The search covered observational literature published from each database inception until February 1, 2023. We analyzed the prevalence of CMBs during the follow-up period, compared future ICH risk between patients with and without baseline CMBs (CMBs presence/absence, ≧5 CMBs), and examined factors influencing ICH occurrence in patients with CMBs. Also studied recurrent stroke during anticoagulation therapy, the risk of future ICH when white matter hyperintensity (WMH) and CMBs coexist, and the effects of anticoagulants Vitamin K Antagonists (VKAs) and Direct oral anticoagulants (DOACs) on future ICH. Results: We included 7 articles involving 5,134 participants. The incidence of CMBs was 24%; baseline CMBs were associated with an increased ICH risk compared to patients without CMBs. ICH–risk was more significant in patients with baseline ≥ 5 CMBs. After anticoagulant therapy, ICH risk was higher than that of recurrent IS. The risk of future ICH was significantly increased with anticoagulant VKAs compared with NOAC. Conclusion: Anticoagulant therapy for ischemic stroke patients with non-valvular AF and CMBs increases future ICH risk. Discontinuing anticoagulation due to ICH risk should be avoided. NOACs are safe and effective for patients with CMBs and IS.